Pengaruh Leverage Terhadap Manajemen Laba Dengan Corporate Governance Sebagai Variabel Pemoderasi - Dewi, Putu Elsa Pratiwi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p19, 2019)
Earnings management is driven by number of factors that are wrong to say leverage. One way to reduce management actions taken by management is the existence of good corporate governance in the company. This study aims to find evidence that is used to influence corporate earnings management in moderating the effect of leverage on earnings management. This research was conducted in all non-financial companies recorded in the Corporate Governance Perception Index (CGPI) in 2011-2016. The method of determining the sample used is purposive sampling. The number of companies that meet the requirements is 5 companies with 30 observations. Data collection is done by non-participant techniques. The data analysis technique used is Moderation Regression Analysis (MRA). Based on the results of the study, namely leverage has a negative effect on earnings management. This study also found that Corporate Governance was able to moderate the influence of leverage on earnings management. Keywords: Earnings Management, Leverage, Corporate Governance